The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2223/jped.2225
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ΔF508 mutation in the cystic fibrosis transmembrane conductance regulator gene among cystic fibrosis patients from a Brazilian referral center

Abstract: Objective: To verify the presence of ΔF508 mutation in the cystic fibrosis transmembrane conductance regulator gene among patients with cystic fibrosis diagnosed by the sweat test for sodium and chlorine and followed at the Pediatric Pneumology Outpatient Clinic of Universidade Estadual de Campinas, Brazil, a referral center for the treatment of cystic fibrosis. Methods:The study analyzed 167 DNA samples from cystic fibrosis patients. Patients' genotype was determined by polymerase chain reaction, and allele a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…For example, among the Brazilian states, we can observe differences in the frequency of F508del. In São Paulo, the frequency is around 40% (Bieger et al, 2012), in Minas Gerais 48% (Perone, Medeiros, Castillo, Aguiar, & Januário, 2010;Raskin et al, 2008), Pará, 23% (De Araújo et al, 2005), and in Rio de Janeiro, ~30% (Cabello et al, 2005;da Silva Martins et al, 2014), different from the frequency observed in Caucasian Europeans that can be of up to 90% (Riordan, 2008). Despite all the efforts to identify new mutations circulating in the country, a large number of variants remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, among the Brazilian states, we can observe differences in the frequency of F508del. In São Paulo, the frequency is around 40% (Bieger et al, 2012), in Minas Gerais 48% (Perone, Medeiros, Castillo, Aguiar, & Januário, 2010;Raskin et al, 2008), Pará, 23% (De Araújo et al, 2005), and in Rio de Janeiro, ~30% (Cabello et al, 2005;da Silva Martins et al, 2014), different from the frequency observed in Caucasian Europeans that can be of up to 90% (Riordan, 2008). Despite all the efforts to identify new mutations circulating in the country, a large number of variants remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In some Caucasian populations, the F508del is present in one or both alleles in ~90% of cases (Riordan, 2008). In Brazil, its frequency varies from 23% to 48% (Bieger, Marson, & Bertuzzo, 2012). This may be due to the migration of different peoples, as well as to the heterogeneous gene flow within the country, occurring among Europeans, Africans, and Amerindians and resulting in a complex Brazilian genetic pool (Cabello, Cabello, Llerena, & Fernandes, 2006).…”
mentioning
confidence: 99%
“…Genomic DNA was obtained by direct extraction from peripheral blood lymphocytes according to standard procedures [ 31 ]. CFTR mutations were determined in the following order: F508del identification using the primers forward 5′-GGC ACC ATT AAA GAA AAT ATC-3′ and reverse 5′-TGG CAT GCT TTG ATG ACG C-3′ [ 25 , 26 ]; CFTR exon sequencing, including exon/intron boundaries, performed as previously described [ 24 , 32 , 33 ]; duplication, deletion, and LOH identification using the SALSA MLPA Kit P091-C1 CFTR-MRC-Holland (MRC-Holland, Willem Schoutenstraat, DL Amsterdam, Netherlands) performed according to the manufacturer instructions; and 1584–18672 pb A>G (intron 10) identification performed as previously described [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, other tools are being studied for CF diagnosis, including the following: (i) the concentrations of chloride and sodium in the saliva [ 21 ]; (ii) β -adrenergic sweat secretion [ 22 ]; (iii) measurements of CFTR-mediated chlorite (Cl) secretion in human rectal biopsies [ 20 ]; (iv) newborn screening (NBS) by assessing immunoreactive trypsinogen (IRT) (that is, following a positive IRT, the sweat test should be performed for CF diagnosis confirmation [ 23 ]); and (v) sequencing of the entire CFTR gene [ 24 ]. In developing countries, a CF diagnosis can be obtained by measuring chloride and sodium levels and usually by performing an F508del (cDNA: c.1521_1523delCTT) mutation screening [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em países economicamente desenvolvidos e com etnias bem definidas é possível identificar mais facilmente todas as mutações presentes no gene CFTR dos pacientes, porém, em populações em desenvolvimento e/ou miscigenadas como a brasileira a caracterização genotípica é mais complexa. No Brasil, a frequência média da F508del é 50%, variando de 8,7% a 50% 10,11,12,13,14,15,16,17 , a depender da região avaliada.…”
Section: Introductionunclassified